Analisis Perkembangan Usaha Kecil dan Menengah di Indonesia - Putri, Osi Hayuni; Zasriati, Masrida; Yadewani, Dorris (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to determine the effect of growth in the number of UKM, growth in UKM Labor Force and growth in UKM Export Value on the growth of UKM GDP contribution in Indonesia and the magnitude of the influence. The research methodology used is a qualitative descriptive and quantitative descriptive approach. The results of the research are that there is an influence of the growth in the number of UKM, the growth of the UKM workforce and the growth of the value of UKM exports on the growth of the GDP contribution of UKM in Indonesia. 81.1%.